THE SIGNIFICANCE OF THE IMAGES OF LIGHT, DARKNESS AND THE MOTH IN TENNESSEE WILLIAMS' A STREETCAR NAMED DESIRE - Alnamer, Abdul Salam Mohamad (Humanities & Social Sciences Reviews, 2020)
Objectives of the study: This study aims to present a critical analysis of the significance of the images of light and darkness in association with the image of the moth in Tennessee Williams' most famous play: A Streetcar Named Desire. It also showcases the tremendous contribution of these images to the vigour and depth of many aspects of the play. Methodology: The article presents a close analysis of textual evidence from the play, following a comparative approach in the study of these images, and is constructed around discussions of their contribution to the thematic and structural aspects of the play. Juxtaposing these images as part of the binary oppositions in the play reveals its richness and depth. Main Findings: The images of light, darkness, and the moth serve a variety of purposes. They are strongly related to the thematic structure of and characterization in the play. They are also important for demonstrating the poetic touch characteristic of the play. The combination of the images illuminates Blanche's dilemma as a broken Southern belle, her frustration, inevitable deterioration, and eventual downfall. Application of the study: This article contributes to the body of the critical study of Williams' drama, in particular, and the study of literature, in general. Given the variety of imagery in the literary canon in all genres, this study can be useful to students and researchers alike in their analyses and appreciation of the significance of imagery in literature. The novelty of this study: This study opens up new venues for the discussion of the play. It also illuminates some aspects of the character of Blanche DuBois which cannot otherwise be illuminated and, at the same time, gives a deep insight into the play as a whole.